Household Expenditure and Food Security Level in North Bengkulu District - Wakarandi, Rolinly; Dewi Arborea, Alvira; Aulia, Maranggi; Sudarma, Rahmat; Reflis, Reflis (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
Food is a fundamental necessity that significantly influences the quality of human resources and regional stability. Bengkulu Province has experienced fluctuating food security indices, ranking 26th nationally in 2021. This study aims to analyze the levels of household expenditure and food security in North Bengkulu Regency. The research employs a descriptive quantitative approach using secondary data from the 2020 National Socio-Economic Survey (SUSENAS), comprising a sample of 620 households. Food security analysis utilizes the Jonsson and Toole (1991) cross-classification method, combining the Food Expenditure Share (PPP) and Dietary Diversity indicators. The results indicate that the majority of households (55%) fall into the high to very high expenditure categories. Regarding food security status, 55% of households are classified as